Expression profiling of microrna genes related to salt stress in banana (Musa Acuminata cv. berangan) roots / Lee Wan Sin - Lee, Wan Sin (2015)

(untitled)
agricultural practices and climate change increase soil salinity, yields are reduced as crops succumb to salinity-induced abiotic stress. Physiological responses to stress are controlled by expression of genes, which in turn are regulated by microRNAs. Since most banana cultivars are salt-sensitive, improved understanding of genetic regulation of abiotic stress responses in banana can support future crop management and improvement. Transcriptome libraries were constructed from salt-stressed and non-salt-stressed banana roots and then sequenced and annotated. Two banana root transcriptomes were assembled into 31,390 unigenes, of which 99.5% were mapped to the reference banana A-genome and 2,993 (9.5%) were found to be differentially expressed upon 300 mM NaCl treatment. Some of the salt stress responsive genes reported in plants were also observed in the salt-stressed banana roots in this study. The functions of these stress responsive genes include stress signaling, transcriptional regulation, DNA repair, transport, stress defence and cell wall modifications. Besides, genes that have not been reported to be responsive to salt stress or abiotic stress were also found in this study. The unannotated genes and genes coding for hypothetical proteins that were differentially expressed in the salt-stressed banana roots are putative novel salt stress responsive genes. We identified 181 orthologous and 56 Musa-specific miRNAs, of which 59 miRNAs, 43 orthologous and 16 Musa-specific, were found to be differentially expressed in the salt-stressed banana roots. MiRNAs responded to salt stress in a dose-dependent manner. Banana roots expressed a unique set of miRNAs in response to salt stress and these miRNAs regulate diverse biological processes including stress signaling, transcriptional and translational regulations, stress defence, transport, cellular homeostasis, metabolisms and other stress-related functions. In addition, a number of iv unannotated genes and genes coding for unknown proteins that are responsive to salt stress were predicted to be regulated by miRNAs. New miRNA-target modules related to salt stress response in banana roots were proposed in this study. This present study may contribute to the understanding of gene regulation and abiotic stress response in banana roots and the high-throughput sequencing data sets generated in this present study may serve as important genetic resources for salt tolerance traits used for functional genomic studies and genetic improvement in banana.